A New Method to Improve the Fracturing Effect of Coal Seams by Using Preset Slots and Induced Stress Shadows. (22nd April 2021) - Li, Li; Zhou, Lei; Li, Honglian; Xia, Binwei; Zhou, Junping
Abstract : Efficient extraction of coal bed methane before coal mining is essential to eliminate the risk of coal-gas outbursts. However, stimulation technologies should be implemented to enhance the conductivity of the coal seam. In this study, we propose a novel method to create a complex fracture network in underground coal mines with the integration of multiple hydraulic slotting and hydraulic fracturing. In this method, hydraulic slots are used to direct hydraulic fractures and initialize branch fractures, while hydraulic fracturing is used to extend the fractures. Given the mutually exclusive and attractive propagation of multiple fractures, a relatively evenly distributed fracture network can be generated. The results show that (1) the dynamically induced stress shadows of hydraulic fractures can cause exclusive and attractive propagation of multiple hydraulic fractures; (2) a preset slot that deviates from the principal stress can direct hydraulic fractures to a certain extent and generate branch fractures; and (3) with a staggered distribution of preset slots, a relatively large volume of the coal seam in both the minimum and maximum horizontal stress directions can be stimulated, creating a complex fracture network including many vertical branch fractures and a large area of horizontally layered directional fractures.